EVALUASI DAMPAK PROGRAM CORPORATE SICIAL RESPONSIBILITY BADAN USAHA MILIK NEGARA (PT INDONESIA POWER) PADA MASYARAKAT LOKAL BANJAR PESANGGARAN (STUDI KASUS : PT INDONESIA PESANGGARAN, DENPASAR-BALI) - Agus Rudiyasa, I Komang; Pascarani, SS, M.Si, Ni Nyoman Dewi; Wismayanti, SE., M.AP, Kadek Wiwin Dwi (CITIZEN CHARTER, 2015)
ABSTRACT The issues of regarding social and environmental responsibility of a company at this time is must be implemented in order to create a harmonious relationship with the people and the environment. Base on conflict between Banjar Pesanggaran people with PT Indonesia Power where the company is carrying out to add machine. These machines had been rejected by Banjar Pesanggaran people for the impact. Therefore, PT Indonesia Power should pay more attention to the Banjar Pesanggaran people and shall carry out responsibilities in accordance with applicable local wisdom in the community. The purpose of this study was to find the answer interrelated relationship between the organizers of the program to all parts of Banjar Pesanggaran people. Then examine the program if it’s in accordance with CSR procedure, the areal condition and local wisdom in Banjar Pesanggaran people. This research uses qualitative descriptive method. To obtain research data observations by looking directly phenomena that happen in the field and do some interviews with sources associated with the programs implemented by PT Indonesia Power and beneficiaries. Then the result of this research is PT Indonesia Power who has understood the appeal of the government in implementing CSR programs and in accordance with applicable of local wisdom in Banjar Pesanggaran people. And the result is people is still not to understand of PT. Indonesia Power’s program, so the PT Indonesia Power must be doing some more sosialitation of their programs. Keywords : Public Policy, Corporate Social Responsibility (CSR), Local Wisdom